2005
DOI: 10.1136/gut.2004.042168
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter species with hepatitis C cirrhosis with or without hepatocellular carcinoma

Abstract: Background and aims: Recent studies have suggested that bacterial coinfection with Helicobacter species in patients already infected with hepatitis C virus (HCV) could be involved in the development of cirrhosis and hepatocellular carcinoma (HCC). A retrospective cross sectional study was performed in order to explore the association between Helicobacter species and HCV associated liver diseases. Methods: The presence of Helicobacter species was tested by polymerase chain reaction on liver samples from four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 33 publications
7
122
1
3
Order By: Relevance
“…[14][15][16] However, the pathological role of chronic H. pylori infection in liver diseases remains controversial. Our earlier report showed that H. pylori promotes hepatic fibrosis in rat and mouse models, in which Goo et al 22 showed that H. pylori infection for 4-months duration caused functional and morphological degenerative changes in hepatocytes with slight focal necrotic and inflammatory changes, in spite of there being no severe hepatitis present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] However, the pathological role of chronic H. pylori infection in liver diseases remains controversial. Our earlier report showed that H. pylori promotes hepatic fibrosis in rat and mouse models, in which Goo et al 22 showed that H. pylori infection for 4-months duration caused functional and morphological degenerative changes in hepatocytes with slight focal necrotic and inflammatory changes, in spite of there being no severe hepatitis present.…”
Section: Discussionmentioning
confidence: 99%
“…13 Reportedly, H. pylori infection occurs with a high frequency in patients with cirrhosis and hepatocellular carcinoma (HCC), which may explain the frequent occurrence of gastroduodenal ulcer in cirrhotic patients. [14][15][16][17] Several studies have shown that H. pylori genomic sequences could be detected in the liver of patients with HCC. 18,19 H. hepaticus, a newly recognized Helicobacter sp., was experimentally proven to cause chronic hepatitis and HCC in mice.…”
mentioning
confidence: 99%
“…106(6): 748-754, September 2011 The hypothesis that Helicobacter spp might be a risk factor for human liver diseases has arisen after the discovery of Helicobacter hepaticus and its association with murine hepatitis and hepatocellular carcinoma (HCC). Subsequent studies in humans have shown the presence of Helicobacter DNA in hepatic tissue of patients with hepatobiliary diseases, mainly cirrhosis and/ or HCC secondary to hepatitis B virus (HBV) and hepatitis C virus (HCV) (Avenaud et al 2000, Dore et al 2002, Fan et al 2002, Verhoef et al 2003, Rocha et al 2005, Pellicano et al 2008. Although these studies have contributed to the debate on the participation of Helicobacter species in the severe human liver disease outcomes, no explanation that justifies the presence of the bacterium in the human liver has yet been proposed.…”
mentioning
confidence: 99%
“…Faecal DNA samples from 20 BN rats were shipped to our laboratory from Taconic Farms after routine testing discovered Helicobacter in mice where the BN rats were co-housed in the same barrier. Samples were screened for Helicobacter species by PCR using 16S rRNA gene genus-specific primers and H. pullorum cytolethal distending toxin B (cdtB) gene speciesspecific primers (Boutin et al, 2010;Fox et al, 1998;Rocha et al, 2005). Samples confirmed as H. pullorum were subjected to restriction fragment length polymorphism (RFLP) analysis following amplification using Helicobacter genus-specific primers.…”
Section: Methodsmentioning
confidence: 99%
“…In another case, H. pullorum was isolated from the faeces of a male with diarrhoea and elevated liver enzymes (Burnens et al, 1994). H. pullorum has also been identified by PCR in humans with inflammatory bowel disease, hepatitis, cholecystitis and hepatocelluar carcinoma (Castéra et al, 2006;Fox et al, 1998;Rocha et al, 2005;Veijola et al, 2007). A recent report identified an association between EHS and Crohn's disease, with H. pullorum being one of the most prevalent EHS identified (Laharie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%